Campus Police Cooperation and Legitimacy: Extending the Procedural Justice Model. Issue 10 (3rd October 2018) - Aiello, Michael F.; Lawton, Brian A.
ABSTRACT: This paper extends the procedural justice model to campus policing, examining both the antecedents of legitimacy as well as the relative influence of student legitimacy evaluations on their likelihood of reporting campus crimes to the public safety department. A simple random sample of 31 undergraduate sections ( n  = 554) responded to a paper survey instrument. Undergraduate respondents indicate general procedural justice ratings are significantly related to their evaluations of campus police (CP) legitimacy. In turn, legitimacy ratings are significantly related to reporting likelihood. However, evaluations of the effectiveness of the CP have a stronger relationship with legitimacy than procedural justice.